2013
DOI: 10.1212/01.wnl.0000435299.57153.f0
|View full text |Cite
|
Sign up to set email alerts
|

MRI and pathology of REM sleep behavior disorder in dementia with Lewy bodies

Abstract: Presence of pRBD is associated with a higher likelihood of DLB and less severe Alzheimer-related pathology in the medial temporal lobes, whereas absence of pRBD is characterized by Alzheimer-like atrophy patterns on MRI and increased phospho-tau burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Since LB or AD-related pathologies are not considered to affect preferentially one hemisphere over another, the ROI-based rates of atrophy were calculated as averages of right and left hemispheric ROIs. The hippocampus and amygdala were chosen for ROI analysis because these structures have received reasonable attention in the literature as proxies of AD and DLB on MRI (Burton, et al, 2012, Burton, et al, 2009, Kantarci, et al, 2012, Murray, et al, 2013, Vemuri, et al, 2011, Whitwell, et al, 2007), and can be consistently quantified with various softwares due to their distinct borders (Fischl, et al, 2002, Patenaude, et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since LB or AD-related pathologies are not considered to affect preferentially one hemisphere over another, the ROI-based rates of atrophy were calculated as averages of right and left hemispheric ROIs. The hippocampus and amygdala were chosen for ROI analysis because these structures have received reasonable attention in the literature as proxies of AD and DLB on MRI (Burton, et al, 2012, Burton, et al, 2009, Kantarci, et al, 2012, Murray, et al, 2013, Vemuri, et al, 2011, Whitwell, et al, 2007), and can be consistently quantified with various softwares due to their distinct borders (Fischl, et al, 2002, Patenaude, et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, greater atrophy in the hippocampus and amygdala has been associated with a high Braak NFT stage (Kantarci, et al, 2012) and tau-NFT density (Murray, et al, 2013) in patients with LB pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy in the limbic, temporal and parietal association cortices on structural MRI is a marker of neurodegeneration associated with tau neurofibrillary tangle pathology of Alzheimer's disease and DLB (Jack et al, 2004;Burton et al, 2009;Murray et al, 2013). In several studies, patients with probable DLB showed an Alzheimer's diseaselike pattern of atrophy (Whitwell et al, 2007b;Sabattoli et al, 2008;Zhong et al, 2014) while autopsy confirmation later showed that the presence of tau neurofibrillary tangles and their Braak stage (Braak and Braak, 1991) of Alzheimer's disease primarily explained the cross-sectional (Burton et al, 2009;Kantarci et al, 2012a;Murray et al, 2013) and longitudinal (Nedelska et al, 2015) atrophy observed in the medial temporal structures.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, while hippocampal phospho-tau burden is associated with hippocampal atrophy, a-synuclein burden does not appear to influence the global hippocampal volume in patients with Lewy body pathology. 9 Therefore preserved hippocampal volumes may predict progression to DLB vs AD in MCI.…”
mentioning
confidence: 99%
“…24 In particular, hippocampal atrophy suggests additional AD-related neurofibrillary tangle pathology in probable DLB cases and may differentiate patients with mixed AD and Lewy body disease pathology from those with DLB. [6][7][8][9] Preservation of hippocampal volumes is also observed in patients with hippocampal sparing AD, 25 therefore is not specific to DLB. We censored individuals who progressed to dementia syndromes other than AD dementia or probable DLB at the time of progression to dementia and several of these patients as well as those who received a clinical diagnosis of probable DLB or AD dementia may have had atypical AD pathology.…”
mentioning
confidence: 99%